2006
DOI: 10.1242/jcs.03014
|View full text |Cite
|
Sign up to set email alerts
|

NFAT3 is specifically required for TNF-α-induced cyclooxygenase-2 (COX-2) expression and transformation of Cl41 cells

Abstract: Journal of Cell Science 119 (14)Journal of Cell Science . Effects of IL-1beta, TNF-alpha, and macrophage migration inhibitory factor on prostacyclin synthesis in rat pulmonary artery smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 60 publications
1
49
0
Order By: Relevance
“…In addition, hypertonic saline has been reported to induce COX-2 in rat macrophages [87] and human ECs [88]. The participation of NFAT transcription factors in COX-2 activation was also already shown in several additional cell types [89][90][91][92][93][94]. In fact, previous research had shown that the angiogenic signaling involved in the induction of COX-2 by VEGF in human ECs requires the activation of NFAT proteins [91].…”
Section: Biophysical Pathways: the Role Of Hyperosmolar Stressmentioning
confidence: 84%
“…In addition, hypertonic saline has been reported to induce COX-2 in rat macrophages [87] and human ECs [88]. The participation of NFAT transcription factors in COX-2 activation was also already shown in several additional cell types [89][90][91][92][93][94]. In fact, previous research had shown that the angiogenic signaling involved in the induction of COX-2 by VEGF in human ECs requires the activation of NFAT proteins [91].…”
Section: Biophysical Pathways: the Role Of Hyperosmolar Stressmentioning
confidence: 84%
“…Although the implications of COX-2 in cell proliferation, cell transformation, and carcinogenesis have been evidential in most of the previous studies (4,20), there is still some evidence showing that COX is not involved in biological effects in some systems (38,39). For example, Lu et al (38) has reported that overexpressing human cDNA of COX-2 in human breast epithelial cells inhibited cell proliferation by delaying cell cycle progression through the G 1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…The COX-2 -luciferase reporter plasmid containing the upstream 5 ¶-flanking region of the COX-2 gene promoter linked to the luciferase reporter was described in our previous studies (20). A pcDNA3.…”
Section: Plasmids and Construction Of Sirna Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…MSK has also been implicated in cancer-related inflammation through COX2 expression. It has been observed that MSK-mediated COX2 expression in mouse epidermal cells induces neoplastic transformation (Yan et al, 2006). MSK recruitment and H3S10 and H3S28 phosphorylation occur at the upstream regulatory promoter region of COX2 in mouse fibroblasts in addition to the recruitment of chromatin remodeling factors and transcriptional activation histone marks at these sites (Drobic et al, 2010).…”
Section: The Role Of Mitogen and Stress Activated Kinase (Msk) In Brementioning
confidence: 99%